2018
DOI: 10.1002/jcb.27474
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9‐mediated sheep MSTN gene knockout and promote sSMSCs differentiation

Abstract: Myostatin (MSTN) is an important gene involved in the regulation of embryonic muscle cells and adult muscle development; it has a good application prospect in transgenic animal production by improving the yield of muscle. The purpose of this study is to construct MSTN gene knockout vector using clustered regularly interspaced short palindromic repeats ( CRISPR)/CRISPR‐associated protein 9 ( Cas9). The knockout efficiency was evaluated in sheep ear fibroblasts (SEFs) by cleavage activity of transcription of gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 17 publications
(32 reference statements)
1
22
0
Order By: Relevance
“…Moreover, disrupting the normal function of MSTN in sheep skeletal muscle satellite cells (sSMSCs) has been shown to promote sSMSC differentiation in both number and length. This study has also reported the generation of MSTN -disputed sheep using SCNT from CRISPR/Cas9 transfected ear fibroblasts (Zhang et al, 2018c). A further and more recent report, published by our team, described the application of CRISPR/Cas9-based base editors for the introduction of a point mutation within the suppressor of cytokine signaling 2 (SOCS2) gene in sheep (Zhou et al, 2019).…”
Section: Applications Of Crispr/cas9 In Sheep and Goatsmentioning
confidence: 89%
“…Moreover, disrupting the normal function of MSTN in sheep skeletal muscle satellite cells (sSMSCs) has been shown to promote sSMSC differentiation in both number and length. This study has also reported the generation of MSTN -disputed sheep using SCNT from CRISPR/Cas9 transfected ear fibroblasts (Zhang et al, 2018c). A further and more recent report, published by our team, described the application of CRISPR/Cas9-based base editors for the introduction of a point mutation within the suppressor of cytokine signaling 2 (SOCS2) gene in sheep (Zhou et al, 2019).…”
Section: Applications Of Crispr/cas9 In Sheep and Goatsmentioning
confidence: 89%
“…In broiler growth and development, the number of muscle fibers is mainly determined in the embryonic stage [ 34 ]. At the same time, myostatin ( MSTN ) is an important gene regulating embryonic muscle cells and adult muscle development, so MSTN is crucial for skeletal muscle growth and development [ 35 ]. Studies have shown that recombinant myostatin protein can inhibit C2C12 mouse myoblasts proliferation, DNA synthesis, and protein synthesis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers generated marker-gene-free MSTN biallelic mutation cattle via ZFNs combined with SCNT technology, which exhibited the double-muscled phenotype with about half the level of MSTN protein with an intact C-terminal domain estimated by ELISA analysis [4] . MSTN-KO goats [24,52] and sheep [53] have also been generated via CRISPR/Cas9.…”
Section: Milk and Meatmentioning
confidence: 99%